Is there a correlation between preoperative neutrophil-to-lymphocyte, platelet-to-lymphocyte, and lymphocyte-to-monocyte ratios and postoperative pain in video-assisted thoracoscopic surgery?. Issue 21 (27th May 2022) - Ülger, Gülay; Baldemir, Ramazan; Zengin, Musa; Sazak, Hilal; Alagöz, Ali
Abstract : Abstract: Many thoracic surgery procedures are now performed with video-assisted thoracoscopic surgery (VATS). Postoperative pain is a common condition in patients undergoing VATS. In this study, we aimed to investigate whether neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), and lymphocyte-to-monocyte ratio (LMR) are effective in evaluating postoperative pain in patients undergoing VATS. This prospective observational study was performed between March 2021 and September 2021 at a tertiary thoracic surgery center. The study included patients who had undergone elective VATS. Preoperative and postoperative NLR, PLR, LMR, hemogram values and postoperative visual analog scale (VAS) were recorded. A total of 105 patients were analyzed. A positive correlation was observed between postoperative monocyte, neutrophils and VAS resting and VAS cough levels in the early postoperative period. No significant correlation was found between preoperative and postoperative NLR, PLR, and LMR values and VAS rest and VAS cough values. When compared to the preoperative period, a negative correlation was found between the change in the postoperative LMR value and the VAS rest and VAS cough values in the early postoperative period. When compared to the preoperative period, the change in postoperative neutrophil, postoperative monocytes, and postoperative LMR values in patients undergoing VATS in thoracic surgery can be used as a guide in the objective evaluation of postoperative acute pain. It is the belief of the researchers that comprehensive new studies on this subject will contribute significantly to the determination of objective criteria in postoperative pain evaluation.